Cultural Conflict and Analysis of Iqbal's Critique on Educational System of East and West - Syed Shiraz Ali Zaidi (بازیافت, 2021)
The education System of a nation is product of its culture. Every nation wants to nurture its children according to its cultural heritage. culture plays an important role in shaping the education system. That is why, sometimes the education system of one nation can be very harmful to the national existence of another nation. As we saw in colonial period that the Western education system was not only an educational but also a cultural invasion. Especially in Subcontinent this invasion proved very harmful for the identity of Muslims as nation. So, many intellectuals came forward as critics of the Western education, but usually their criticism seems to be exaggerated. In this scenario, Iqbal was the only intellectual whose criticism on Western education seems to be balanced, because he not only criticizes the Western education system but also exposes the Eastern education system of the time.